Putin and North Korea: exploring Russian interests around the peninsula - Westermann, Jacqueline; Australian Strategic Policy Institute (Barton, ACT : Australian Strategic Policy Institute, 2018)
This paper highlights different motivations that the Russian Government has to potentially play a bigger role in discussions and negotiations on security issues on the peninsula. The findings are based on analysis of official statements by Russian Government officials during 2017 and interviews with Russian North Korea experts conducted by the author in February 2018. The paper explores geopolitical, strategic, economic and national policy motivations that have led to Moscow increasingly looking east.
Keywords: National security -- Korea (North); Political leadership -- Korea (North); Diplomatic relations; Military policy; National security; Political leadership; Politics and government; Korea (North) -- Foreign relations -- Russia (Federation); Korea (North) -- Foreign relations; Korea (North) -- Military policy; Korea (North) -- Politics and government; Russia (Federation) -- Foreign relations -- Korea (North); Russia -- Military policy; United States -- Military policy; Korea (North); Russia (Federation); Russia; United States; Australian